Continuing mortality of vultures in India associated with illegal veterinary use of diclofenac and a potential threat from nimesulide. Issue 1 (20th May 2015) - Cuthbert, Richard J.; Taggart, Mark A.; Saini, Mohini; Sharma, Anil; Das, Asit; Kulkarni, Mandar D.; Deori, Parag; Ranade, Sachin; Shringarpure, Rohan N.; Galligan, Toby H.; Green, Rhys E.
Abstract: The collapse of South Asia's Gyps vulture populations is attributable to the veterinary use of the non-steroidal anti-inflammatory drug (NSAID) diclofenac. Vultures died after feeding on carcasses of recently-medicated animals. The governments of India, Nepal and Pakistan banned the veterinary use of diclofenac in 2006. We analysed results of 62 necropsies and 48 NSAID assays of liver and/or kidney for vultures of five species found dead in India between 2000 and 2012. Visceral gout and diclofenac were detected in vultures from nine states and three species: Gyps bengalensis, Gyps indicus and Gyps himalayensis . Visceral gout was found in every vulture carcass in which a measurable level of diclofenac was detected. Meloxicam, an NSAID of low toxicity to vultures, was found in two vultures and nimesulide in five vultures. Nimesulide at elevated tissue concentrations was associated with visceral gout in four of these cases, always without diclofenac, suggesting that nimesulide may have similar toxic effects to those of diclofenac. Residues of meloxicam on its own were never associated with visceral gout. The proportion of Gyps vultures found dead in the wild in India with measurable levels of diclofenac in their tissues showed a modest and non-significant decline since the ban on the veterinary use of diclofenac. The prevalence of visceral gout declined less, probably because some cases of visceral gout from 2008 onwards were associated with nimesulide rather than diclofenac. Veterinary use of nimesulide is a potential threat to the recovery of vulture populations.